2021
DOI: 10.1111/1751-7915.13877
|View full text |Cite
|
Sign up to set email alerts
|

Development of a free radical scavenging bacterial consortium to mitigate oxidative stress in cnidarians

Abstract: Corals are colonized by symbiotic microorganisms that profoundly influence the animal's health. One noted symbiont is a single-celled alga (in the dinoflagellate family Symbiodiniaceae), which provides the coral with most of its fixed carbon. Thermal stress increases the production of reactive oxygen species (ROS) by Symbiodiniaceae during photosynthesis. ROS can both damage the algal symbiont's photosynthetic machinery and inhibit its repair, causing a positive feedback loop for the toxic accumulation of ROS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 126 publications
(135 reference statements)
0
21
0
Order By: Relevance
“…Alteromonadaceae belong to a diverse group of heterotrophic gammaproteobacteria known to associate with marine hosts and nutrient-rich environments. Members of this group tolerate relatively high temperatures and have been used in coral probiotic studies as coral-associated bacteria capable of scavenging free radicals [ 66 ] and therefore could provide similar benefits in shallow, high-light environments. Similarly, Acidimicrobiales are known to be planktonic free-living photo-heterotrophs found in both temporal and tropical photic zones [ 67 ] and are associated with dissolved organic matter (DOM) in marine environments [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alteromonadaceae belong to a diverse group of heterotrophic gammaproteobacteria known to associate with marine hosts and nutrient-rich environments. Members of this group tolerate relatively high temperatures and have been used in coral probiotic studies as coral-associated bacteria capable of scavenging free radicals [ 66 ] and therefore could provide similar benefits in shallow, high-light environments. Similarly, Acidimicrobiales are known to be planktonic free-living photo-heterotrophs found in both temporal and tropical photic zones [ 67 ] and are associated with dissolved organic matter (DOM) in marine environments [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…These approaches may address the issues of dilution and inadequate uptake of putative beneficial bacteria by coral and warrant further investigation. Furthermore, of the nearly 1000 bacteria isolated from E. diaphana (Dungan et al 2021a) and the thousands of bacterial cells they can carry (Costa et al 2021), only 12 were used in this study. More work is needed to explore the potential beneficial roles of the other bacteria, which may be possible with advances in metagenomic sequencing and the assembly of bacterial metagenome-assembled genomes.…”
Section: Limitations Of the Study And Recommendations For Future Micr...mentioning
confidence: 99%
“…Individual isolates were selected and grown to log phase in 50 ml of modified R2A broth (mR2A; Table S1). The FRS phenotype of each high and low FRS bacterial strain was similar when incubated at 26°C or 37°C (Table S2; Dungan et al 2021a). Since the bacteria grew more rapidly at 37°C, cultures were incubated at 37°C for 48 h at 150 rpm in an orbital incubator (OM11, Ratek).…”
Section: Selection Of Free Radical Scavenging Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Microbiome manipulation is one of several avenues that are currently being pursued in order to mitigate coral bleaching [40,53,54,[167][168][169][170]. As excess ROS production by Symbiodiniaceae is one of the main causes of coral bleaching [34,[36][37][38], it was postulated that treating corals with bacteria with a high ROS-scavenging ability could mitigate coral bleaching [171]. Proof of concept studies have confirmed that the coral microbiome can be modified [172,173], without specifically targeting ROS scavenging, but only three studies so far have actually trialed probiotics to mitigate coral bleaching [174][175][176].…”
Section: Applications Involving Coral-associated Intracellular Bacteria To Help Save Coral Reefsmentioning
confidence: 99%